Microcrystalline Wax

The hydroisomerization of Fischer-Tropsch waxes using a specific catalyst produces microcrystalline waxes with extended carbon chains and high branched paraffins, addressing impurity and chain length limitations, enhancing their performance in various applications.

JP7610579B2Active Publication Date: 2025-01-08SHELL INTERNATIONALE RESEARCH MAATSCHAPPIJ BV
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2022507717
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2019-08-08
Filing Date
2020-08-03
Publication Date
2025-01-08
Estimated Expiration
2040-08-03

AI Technical Summary

Technical Problem

Existing processes for producing microcrystalline waxes from petroleum residues and Fischer-Tropsch synthesis yield waxes with impurities, limited carbon chain lengths, and insufficient amounts of polymethyl branched paraffins, which affect their performance in applications like petroleum jelly and hot melt adhesives.

Method used

A process that involves hydroisomerization of Fischer-Tropsch waxes using a catalyst with a molecular sieve and Group VIII metal to produce microcrystalline waxes with carbon numbers greater than 120, high polymethyl branched paraffins, and adjusted crystallinity, enabling improved oil binding capacity and reduced impurities.

Benefits of technology

The resulting microcrystalline waxes exhibit enhanced properties for applications such as petroleum jelly, hot melt adhesives, and automotive polishes, with improved oil binding capacity and reduced need for additional ingredients, while preserving the production of other Fischer-Tropsch derived products.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007610579000005
    Figure 0007610579000005
  • Figure 0007610579000006
    Figure 0007610579000006
  • Figure 0007610579000001
    Figure 0007610579000001
Patent Text Reader

Abstract

The present invention provides a microcrystalline wax having a penetration greater than 1 at 25°C according to ASTM D-1321, a crystallinity of 5-70% according to XRD, an initial boiling point less than 500°C, a freezing point in the range of 60-120°C, and an oil content greater than 2 wt% according to ASTM D-721, wherein the microcrystalline wax has a maximum C40 fraction with at least 5 wt% multi-methyl-branched paraffins as determined by GCxGC.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to microcrystalline wax, a process for preparing the microcrystalline wax, petroleum jelly containing the microcrystalline wax, and the use of the microcrystalline wax in petroleum jelly, hot melt adhesives, as a gloss enhancer, automotive and shoe polishes, and as protection for emulsions and PVC reactors. [Background technology]

[0002] It is known to prepare microcrystalline waxes by solvent dewaxing of fractions of petroleum residues by vacuum distillation. The production of microcrystalline waxes is usually associated with plants producing Group I base oils. Examples of such processes are described in Ullman's Encyclopedia of Industrial Chemistry, Wiley-VDH Verlag, 2000. These microcrystalline waxes may contain a significant fraction boiling above 750°C.

[0003] The problem with the process of producing microcrystalline waxes from petroleum residues is that, although this process provides microcrystalline waxes with favorable properties for many applications, they contain impurities such as (poly)aromatics, sulfur, nitrogen, and oxygen compounds. Moreover, the production of microcrystalline waxes from petroleum residues is low when the complexes of Group I base oils are closed due to the low demand for these base oils.

[0004] It is also known to prepare waxes from products obtained from the Fischer-Tropsch process, as described, for example, in WO02 / 096842A2, which discloses a process for preparing microcrystalline waxes from starting materials having carbon atoms ranging from 20 to 105. The microcrystalline waxes according to WO02 / 096842A2 have a high oil content and a low amount of multi-methyl branched paraffins (in other words, they do not have highly branched isoalkanes).

[0005] The problem with the process as disclosed in WO02 / 096842A2 is that, although the process provides microcrystalline wax, the microcrystalline wax having molecules with carbon numbers greater than 120 is not produced. Furthermore, the process disclosed in WO02 / 096842A2 produces microcrystalline wax having a small amount of multi-methyl branched paraffins (in other words, not having highly branched isoalkanes). Multi-methyl branched paraffins can help improve the oil-binding ability of microcrystalline wax in applications such as petroleum jelly.

[0006] EP1409613B1 discloses a process for preparing microcrystalline wax by contacting a feed containing at least 80 wt.% normal paraffins under hydroisomerization conditions with a catalyst comprising a noble metal and a porous silica-alumina support.

[0007] A problem with the process as disclosed in EP 1 409 613 is that the microcrystalline wax is obtained by total hydroisomerization of the wax product obtained in the Fischer-Tropsch synthesis. As a result, the production of other Fischer-Tropsch derived products is excluded by the process disclosed in EP 1 409 613. Furthermore, microcrystalline waxes having a freezing point in the range of 95-120 are obtained. Summary of the Invention

[0008] It is an object of the present invention to solve or minimise at least one of the above problems.

[0009] It is a further object of the present invention to provide microcrystalline waxes which can be advantageously used in applications such as petroleum jelly, hot melt adhesives, as gloss enhancers, automotive and shoe polishes, and as protection for emulsions and PVC reactors.

[0010] Furthermore, it is an object of the present invention to provide an efficient method for preparing microcrystalline waxes having molecules with carbon numbers greater than 120 and large amounts of multi-methyl branched paraffins.

[0011] One of the above or other objects is achieved in accordance with the present invention by providing a microcrystalline wax having a penetration of greater than 1 at 25°C according to ASTM D-1321, a crystallinity of 5-70% according to XRD, an initial boiling point of less than 500°C, a freezing point in the range of 60-120°C, an oil content of greater than 2% by weight according to ASTM D-721, the microcrystalline wax having a maximum C40 fraction with at least 5% by weight of multi-methyl branched paraffins as determined by GCxGC.

[0012] It has now surprisingly been found, in accordance with the present invention, that microcrystalline waxes can be advantageously used in some microcrystalline wax applications.

[0013] An important advantage of the present invention is that the microcrystalline wax can be advantageously used as a gloss enhancer, automotive and shoe polish, and as protection for emulsions and PVC reactors in applications such as petroleum jelly, hot melt adhesives, etc. The high carbon chain length distribution and large amount of multi-methyl branched paraffins of the microcrystalline wax reduces the use of additional components in various applications.

[0014] In addition, the high melting point and high penetration of microcrystalline waxes make microcrystalline paraffin an ideal candidate for use in hot melt adhesives.

[0015] As explained above, a key advantage of the present invention is that microcrystalline waxes having molecules with carbon numbers greater than 120 and large amounts of multi-methyl branched paraffins provide good oil binding capacity when used in microcrystalline wax applications such as petroleum jelly where oil and wax are combined.

[0016] In another embodiment of the present invention, a process for preparing microcrystalline wax is provided. The advantage of the process according to the present invention is that the production of microcrystalline wax does not have to be at the expense of other Fischer-Tropsch derived products, since the microcrystalline wax is not prepared from the hydroisomerization of the entire wax product obtained in the Fischer-Tropsch synthesis, but from a fraction of the Fischer-Tropsch derived wax, which has a freezing point between 60 and 120°C, although the freezing point of the obtained microcrystalline wax may be below 95°C. In contrast to the preparation of microcrystalline wax from crude oil, in the process according to the present invention, the degree of isomerization of the microcrystalline wax can be adjusted.

[0017] An added benefit is that Fischer-Tropsch waxes that would otherwise not be able to find an outlet can now be converted into highly valuable microcrystalline waxes.

[0018] In a further embodiment of the present invention, there is provided a petroleum jelly comprising the Fischer-Tropsch microcrystalline wax according to the present invention and further containing a Fischer-Tropsch derived wax, and a Fischer-Tropsch derived waxy raffinate, the advantage of which is that it is an all-GTL petroleum jelly with very low contamination levels, which is key for cosmetic applications.

[0019] The figures in the drawings illustrate one or more implementations according to the present teachings, by way of example only, and not by way of limitation, in which like reference numbers refer to the same or similar elements. [Brief description of the drawings]

[0020] [Figure 1] The boiling point distribution of a Fischer-Tropsch wax having a freezing point of 105°C, a product obtained by hydroisomerization at a temperature of 317°C, and a product obtained by hydroisomerization at a temperature of 340°C. [Diagram 2] FIG. 2 is the smearability of several petroleum jelly compositions. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0021] The present disclosure is not limited to the embodiments as described above and the appended claims. Many modifications are possible and the features of each embodiment can be combined.

[0022] According to the present invention, there is provided a microcrystalline wax having a penetration of greater than 1 at 25°C according to ASTM D-1321, a crystallinity of 5-70% according to XRD, an initial boiling point of less than 500°C, a freezing point in the range of 60-120°C, an oil content of greater than 2% by weight according to ASTM D-721, wherein the microcrystalline wax has a maximum C40 fraction with at least 5% by weight of multi-methyl branched paraffins as determined by GCxGC.

[0023] The microcrystalline wax is mainly composed of paraffins. The microcrystalline wax according to the invention is composed of more than 40% by weight of isoparaffins, preferably more than 60% by weight of isoparaffins.

[0024] Microcrystalline waxes are known and are described, for example, in WO 02 / 096842 A2 and EP 1 409 613 B1.

[0025] Preferably, the fraction of the microcrystalline wax with a maximum C40 has at least 5% by weight of multi-methyl-branched paraffins as determined by GCxGC. Suitably, the fraction with a maximum C40 carbon chain length has at least 10% by weight of multi-methyl-branched paraffins as determined by GCxGC, and less than 90% by weight, preferably less than 80% by weight of multi-methyl-branched paraffins. The fraction with a maximum C40 is preferably a fraction with a carbon chain length of C8 to C40.

[0026] Also, the microcrystalline wax according to the invention has a penetration according to ASTM D-1321 of more than 1 at 25° C. Preferably, the microcrystalline wax according to the invention has a penetration according to ASTM D-1321 of more than 10 at 25° C., more preferably more than 20, up to a maximum of 250. For the microcrystalline wax according to the invention, a penetration of up to 250 is indicated, since 250 is the limit of ASTM D-1321.

[0027] Furthermore, the microcrystalline wax according to the present invention has a crystallinity according to XRD of 5-70%, preferably 5-60%, more preferably 10-50%, even more preferably 10-30%.

[0028] Preferably, the microcrystalline wax according to the present invention has an initial boiling point of more than 100° C. Suitably, the microcrystalline wax according to the present invention has an initial boiling point of more than 150° C., preferably more than 175° C., more preferably more than 200° C. The final boiling point of the microcrystalline wax according to the present invention is more than 730° C., preferably more than 750° C. The final boiling point of the microcrystalline wax is related to the boiling points of the molecules in the microcrystalline wax that have carbon numbers of 105 (730° C.) and 120 (750° C.), respectively.

[0029] Moreover, the microcrystalline wax according to the present invention has a solidification point in the range of 60 to 120° C. Preferably, the microcrystalline wax according to the present invention has a solidification point in the range of 60 to 105° C., more preferably 60 to 95° C., and even more preferably 60 to 85° C. according to ASTM D-938.

[0030] Furthermore, the microcrystalline wax according to the invention has a weight ratio of isoalkanes that is greater than the weight ratio of n-alkanes.

[0031] Preferably, the amount of isoalkanes is greater than 40% by weight, based on the total amount of paraffins.In contrast to crude oil-derived microcrystalline waxes, the microcrystalline waxes according to the invention have very low amounts of naphthenes and aromatics.

[0032] The microcrystalline wax has a kinematic viscosity at 100° C. according to ASTM D445 greater than 12 cSt, preferably in the range of 12 to 30 cSt.

[0033] In a particular embodiment, the microcrystalline wax has a kinematic viscosity of 18 to 30 cSt at 100° C. according to ASTM D445.

[0034] The microcrystalline wax according to the invention is preferably a Fischer-Tropsch derived microcrystalline wax.

[0035] The Fischer-Tropsch derived microcrystalline wax is derived from a Fischer-Tropsch process. Fischer-Tropsch product streams are known in the art. The term "Fischer-Tropsch derived" means that the microcrystalline wax is a Fischer-Tropsch process or is derived from a Fischer-Tropsch process. The Fischer-Tropsch derived microcrystalline wax may also be referred to as a GTL (Gas-to-Liquids) product. An example of a Fischer-Tropsch process is shown in WO2002 / 102941, EP1498469, and WO2004 / 009739, the teachings of which are incorporated by reference.

[0036] In a further aspect, the present invention relates to a process for preparing a microcrystalline wax, the process comprising at least the following steps: (a) providing a FT wax having a carbon chain length distribution in the range of 20 to more than 120 and a crystallinity according to XRD of more than 75%, wherein at least 1 wt. % of the FT wax has a carbon chain length of more than 120; (b) a pore size of 5 to 7 angstroms and a SiO2 content of at least 25, preferably 50 to 180; 2 / AlO 3 and a Group VIII metal, at a temperature in the range of 200-400°C, a pressure of 1-25 MPa, and a WHSV of 0.1-5 kg / l / h to obtain a microcrystalline wax having a penetration of greater than 1 at 25°C according to ASTM D-1321, a crystallinity of 5-70% according to XRD, an initial boiling point of less than 500°C, a freezing point in the range of 60-120°C, an oil content of greater than 2 wt% according to ASTM D-721, wherein the microcrystalline wax has a maximum C40 fraction with at least 5 wt% multi-methyl branched paraffins as determined by GCxGC.

[0037] In step (a) of the process according to the invention, a Fischer-Tropsch wax is provided having a carbon chain length distribution in the range of 20 to more than 120 and a crystallinity according to XRD of more than 75. The part "having a carbon chain length distribution in the range of 20 to more than 120" means having molecules with carbon atoms in the range of 20 to more than 120 carbon atoms per molecule. Preferably, the FT wax has molecules with a carbon number of more than 120. The boiling point of the molecule with a carbon number of 120 is 750°C.

[0038] The Fischer-Tropsch wax provided in step (a) is derived from a Fischer-Tropsch process. Fischer-Tropsch wax is known in the art. The term "Fischer-Tropsch wax" refers to a synthesis product of the Fischer-Tropsch process. In the Fischer-Tropsch process, synthesis gas is converted into a synthesis product. Synthesis gas or syngas is a mixture of hydrogen and carbon monoxide obtained by conversion of a hydrocarbonaceous feedstock. Suitable feedstocks include natural gas, crude oil, heavy oil fractions, coal, biomass, and lignite. Fischer-Tropsch products derived from a hydrocarbonaceous feedstock, usually in the gas phase, are sometimes referred to as GTL (Gas-to-Liquids) products. The preparation of Fischer-Tropsch wax is described, for example, in WO9612778.

[0039] Preferably, at least 1 wt.-% of the FT wax provided in step (a) has a carbon number greater than 120, more preferably at least 3 wt.-%, even more preferably at least 5 wt.-%, and most preferably at least 7 wt.-%.

[0040] In step (b), a pore size of 5-7 Å and an SiO 2 content of at least 25, preferably 50-180 are used. 2 / AlO 3The FT wax is subjected to a hydroisomerization step using a catalyst comprising a molecular sieve having a ratio of 0.1 to 0.5% by weight and a Group VIII metal at a temperature in the range of 200-400°C, a pressure of 1-25 MPa and a WHSV of 0.1-5 kg / l / h. Preferably, the FT wax is subjected to hydroisomerization at a temperature in the range of 270-400°C, preferably in the range of 271-380°C, even more preferably in the range of 275-350°C.

[0041] The hydroisomerization of FT wax is described, for example, in EP1498469.

[0042] A suitable catalyst for the hydroisomerization step in step (b) of the present invention is a dewaxing catalyst.

[0043] Suitably the catalyst used in step (b) of the process according to the invention comprises a molecular sieve having a pore size of from 5 to 6.6 Angstroms.

[0044] Preferably, the dewaxing catalyst is a heterogeneous catalyst comprising a molecular sieve, more preferably a 10- or 12-ring molecular sieve having a pore size of 5-6.6 Angstroms, preferably a one-dimensional 10- or 12-ring molecular sieve having a pore size of 5-6.6 Angstroms, more preferably a one-dimensional 10- or 12-ring molecular sieve having a pore size of 5-6.2 Angstroms, in combination with a metal having a hydrogenation function, such as a Group VIII metal. The pore sizes indicated are taken from the 6 th It is related to the maximum pore diameter as given in the revised edition of the Atlas of Zeolite Framework Types.

[0045] Preferably, the hydroisomerization in step (b) is carried out in the presence of a catalyst comprising a molecular sieve and a Group VIII metal, the molecular sieve being selected from the group consisting of MTW, MTT, TON type molecular sieves, ZSM-48 and EU-2.

[0046] In the present invention, references to ZSM-48 and EU-2 are used to indicate that all zeolites belonging to the ZSM-48 family of disordered structures, also referred to as the *MRE family and described in the Catalog of Disorder in Zeolite Frameworks, published in 2000 by the Structure Commission of the International Zeolite Association, can be used. Even if EU-2 is considered to be different from ZSM-48, both ZSM-48 and EU-2 can be used in the present invention. The zeolites ZBM-30 and EU-11 are very similar to ZSM-48 and are considered to be members of the ZSM-48 family of zeolites whose structures belong to the ZSM-48 family. In the present application, any reference to ZSM-48 zeolite is a reference to ZBM-30 and EU-11 zeolites.

[0047] In addition to ZSM-48 and / or EU-2 zeolites, further zeolites can be present in the catalytic composition, especially if it is desired to modify its catalytic properties. It has been found to be advantageous to present the zeolite ZSM-12, a zeolite defined in the Database of Zeolite Structures published in 2007 / 2008 under the commission of the Structure Commission of the International Zeolite Association.

[0048] Suitable Group VIII metals are nickel, cobalt, platinum and palladium. Preferably, the Group VIII metal is platinum or palladium.

[0049] The dewaxing catalyst also preferably comprises a binder. The binder may be non-acidic. Examples of suitable binders are clay, silica, titania, zirconia, alumina, mixtures and combinations of the above, and other binders known to those skilled in the art.

[0050] Preferably, the catalyst comprises a silica or titania binder.

[0051] The preparation of the dewaxing catalyst for the hydroisomerization in step (b) is described, for example, in WO2015 / 063213.

[0052] Step (b) yields a microcrystalline wax having a large amount of multi-methyl branched paraffins, a penetration greater than 1 at 25°C according to ASTM D-1321, a crystallinity index of 5-70 according to XRD, an initial boiling point below 500°C and a freezing point in the range of 60-120°C, and an oil content of greater than 2 wt% according to ASTM D-721.

[0053] Suitably, the fraction of the microcrystalline wax according to the invention having up to 40 carbon atoms comprises, as determined by GCxGC, at least 5% by weight, preferably at least 10% by weight, more preferably at least 25% by weight, but less than 90% by weight, preferably less than 80% by weight, of multiply methyl-branched paraffins. By multiply methyl-branched paraffins is meant paraffins having two or more methyl branches, such as dimethyl paraffins, trimethyl paraffins, tetramethyl paraffins, etc. Usually, this fraction having up to 40 carbon atoms also contains small amounts of paraffins having other branches than methyl, such as ethyl or propyl. The fraction having up to 40 carbon atoms is preferably a fraction having a carbon chain length between C8 and C40.

[0054] The microcrystalline wax obtained in step (b) has a penetration index of 1 to more than 250, preferably 5 to more than 250, more preferably 10 to more than 250 at 25° C. according to ASTM D-1321.

[0055] Suitably, the crystallinity of the microcrystalline wax obtained in step (b) is, according to XRD, between 5 and 70%, preferably between 5 and 60%, more preferably between 10 and 50%, even more preferably between 10 and 30%.

[0056] Suitably, the initial boiling point of the microcrystalline wax obtained in step (b) is greater than 100° C., preferably greater than 150° C., more preferably greater than 175° C., even more preferably greater than 200° C. Optionally, the microcrystalline wax obtained in step (b) can be subjected to a fractionation step to increase the initial boiling point of the microcrystalline wax.

[0057] The solidification point of the microcrystalline wax obtained in step (b) is in the range of 60 to 120°C, preferably 60 to 105°C, more preferably 60 to 95°C, and even more preferably 60 to 85°C, according to ASTM D-938.

[0058] Furthermore, the oil content of the microcrystalline wax obtained in step (b) is more than 2% by weight, but less than 20% by weight, preferably less than 14% by weight, according to ASTM D-721. Optionally, the microcrystalline wax obtained in step (b) can be subjected to a de-oiling step using a solvent to reduce the oil content of the microcrystalline wax. Suitable solvents and processes for de-oiling are known to those skilled in the art.

[0059] In another aspect, the present invention provides a petroleum jelly comprising the Fischer-Tropsch microcrystalline wax according to the present invention and further comprising a Fischer-Tropsch derived wax, and a Fischer-Tropsch derived waxy raffinate or a Fischer-Tropsch derived base oil. Typically, in the petroleum jelly, the Fischer-Tropsch derived wax functions as the wax and the Fischer-Tropsch derived waxy raffinate and the Fischer-Tropsch derived base oil function as the oil.

[0060] Preferably, the microcrystalline wax used in petroleum jelly is obtained according to the method of the present invention.

[0061] Suitably the Fischer-Tropsch derived wax has a freezing point in the range of 30 to 70° C. Preferably the Fischer-Tropsch derived wax has a freezing point of 50° C. The preparation of Fischer-Tropsch wax is described, for example, in WO 2016 / 107864.

[0062] The preparation of Fischer-Tropsch derived waxy raffinates is described, for example, in US 2007 / 0193923.

[0063] Preferably, the amount of microcrystalline wax is from 20 to 100 wt.-%, the amount of Fischer-Tropsch derived wax is from 0 to 50 wt.-% and the amount of waxy raffinate or base oil is from 0 to 50 wt.-%, based on the total amount of microcrystalline wax, Fischer-Tropsch derived wax, and waxy raffinate or base oil in the petroleum jelly.

[0064] In a further aspect, the present invention provides the use of the petroleum jelly according to the present invention in a cosmetic product, a pharmaceutical product, a product for filling cables, or a filled cable product.

[0065] In another aspect, the present invention provides the use of the microcrystalline wax according to the present invention in petroleum jelly, hot melt adhesives, as a gloss enhancer, car and shoe polishes, as emulsions and PVC reactor protection.

[0066] To aid in a better understanding of the invention, examples of specific aspects of some embodiments are given below, which should in no way be read as limiting or defining the scope of the invention. The following describes an embodiment. Aspect 1 A microcrystalline wax having a penetration of greater than 1 at 25°C according to ASTM D-1321, a crystallinity of 5-70% according to XRD, an initial boiling point of less than 500°C, a freezing point in the range of 60-120°C, and an oil content of greater than 2% by weight according to ASTM D-721, said microcrystalline wax having a maximum C40 fraction with at least 5% by weight of multi-methyl branched paraffins as determined by GCxGC. Aspect 2 2. The microcrystalline wax according to embodiment 1, having an initial boiling point above 100° C. Aspect 3 3. The microcrystalline wax according to embodiment 1 or 2, having a weight ratio of isoalkanes greater than the weight ratio of n-alkanes. Aspect 4 A process for preparing a microcrystalline wax, said process comprising at least the following steps: (c) providing an FT wax having a carbon chain length distribution in the range of 20 to >120 and a crystallinity according to XRD of >75%, wherein at least 1 wt. % of said FT wax has a carbon chain length >120; (d) subjecting said FT wax to an isomerization step at a temperature in the range of 200-400°C, a pressure of 1-25 MPa and a WHSV of 0.1-5 kg / l / h using a catalyst comprising a molecular sieve having a pore size of 5-7 Angstroms, a SiO2 / AlO3 ratio of at least 25, preferably 50-180, and a group VIII metal, to obtain a microcrystalline wax having a penetration of more than 1 at 25°C according to ASTM D-1321, a crystallinity of 5-70% according to XRD, an initial boiling point of less than 500°C, a freezing point in the range of 60-120°C, an oil content of more than 2 wt% according to ASTM D-721, said microcrystalline wax having a maximum C40 fraction with at least 5 wt% multi-methyl branched paraffins as determined by GCxGC. Aspect 5 2. A petroleum jelly comprising the microcrystalline wax according to embodiment 1, further comprising a Fischer-Tropsch derived wax, and a Fischer-Tropsch derived waxy raffinate or a Fischer-Tropsch derived base oil. Aspect 6 The petroleum jelly of embodiment 5, wherein the Fischer-Tropsch derived wax has a freezing point of 50° C. Aspect 7 7. The petroleum jelly according to aspect 5 or 6, wherein the amount of microcrystalline wax is 20-100 wt.-%, the amount of Fischer-Tropsch derived wax is 0-50 wt.-%, and the amount of waxy raffinate or base oil is 0-50 wt.-%, based on the total amount of microcrystalline paraffin, Fischer-Tropsch derived wax, and waxy raffinate or base oil in said petroleum jelly. Aspect 8 8. Use of the petroleum jelly according to embodiment 7 in a cosmetic product, a pharmaceutical product, a product for filling cables, or a filled cable product. Aspect 9 Use of the microcrystalline wax according to embodiment 1 in petroleum jelly, hot melt adhesives, as a gloss enhancer, car and shoe polish, as emulsion and PVC reactor protection. EXAMPLES

[0067] Example 1 SX-105, a fraction of hydrogenated and hydrofinished Fischer-Tropsch wax obtained according to WO9612778, was continuously fed to the hydroisomerization step. The feed characteristics are given in Table 1, while the boiling point distribution is shown in Figure 1. The crystallinity (%) by XRD was 100*I 結晶質 / (I 結晶質 +I 非晶質 ), where I 結晶質 is the total area of ​​the crystalline diffraction peaks, and I 非晶質 is the total area of ​​the amorphous peaks (halo).

[0068] In the hydroisomerization step, the feed was contacted with Pd / EU-2 catalyst treated with titania-bound ammonium hexafluorosilicate. Hydroisomerization was carried out at a temperature of 340°C at 70 barg. The remaining conditions were selected to convert less than 15%w of the feed to products boiling below 370°C. The product from the hydroisomerization was sent to a stripper where light gases were removed with nitrogen under conditions selected to obtain more than 95%w of the total hydrocarbon effluent of the hydroisomerization reactor as product. The resulting product (isomerized Fischer-Tropsch microcrystalline wax (isoSX66) with a freezing point of 66°C) was analyzed. The results are listed in Table 1, while the boiling point distribution is shown in Figure 1.

[0069] Example 2 The same SX-105 feed as in Example 1 was continuously fed to the hydroisomerization step, where the feed was contacted with a Pt / ZSM-12 catalyst treated with silica-bound ammonium hexafluorosilicate. The hydroisomerization was carried out at a temperature of 317°C at 38 barg. The remaining conditions were selected to convert less than 5%w of the feed to products boiling below 370°C. The product from the hydroisomerization was sent to a stripper where light gases were removed with nitrogen under conditions selected to obtain more than 95%w of the total hydrocarbon effluent of the hydroisomerization reactor as product. The product (isomerized Fischer-Tropsch microcrystalline wax (isoSX80) with a freezing point of 80°C) was analyzed. The results are listed in Table 1, while the boiling point distribution is shown in Figure 1. [Table 1]

[0070] The products from examples 1 and 2 show that microcrystalline paraffins according to the present invention have been obtained. The products show the presence of paraffins above C120, i.e. boiling above 750°C, freezing point in the range of 60-120°C, XRD crystallinity of 5-70%, penetration of more than 1, oil content of more than 2 wt%, and multi-methyl branched paraffins of more than 5%w: dimethyl branched paraffins (C2-Br) and tri+methyl branched paraffins (>C2-Br).

[0071] Example 2: Commercially available reference products Four commercial samples of petroleum jellies were obtained: Vaseline®, SnowWhite XH by Sonneborn, Carisma Jelly SilkySoft by Alpha Wax, and Merkur 546 by Sasol Wax.

[0072] Example 3: Preparation of Petroleum Jelly Two 20 mL glass vials, each equipped with a magnetic stir bar (PTFE coated, rounded edges, 12 mm long, 3 mm diameter), were charged with an amount of isomerized Fischer-Tropsch derived wax having a freezing point of 80°C, denoted as MCW-1, or an isomerized Fischer-Tropsch derived wax having a freezing point of 70°C, denoted as MCW-2, an amount of Shell Sarawax SX50 (a Fischer-Tropsch derived wax having a freezing point of 50°C, denoted as WAX-1), and an amount of Shell GTL Waxy Raffinate (a Fischer-Tropsch derived waxy raffinate), denoted as OIL-1, or Risella X430 (a Fischer-Tropsch derived base oil), denoted as OIL-2, respectively. The vials were sealed with aluminum screw caps containing septa. The closed vials were placed in an aluminum heating block, preheated to 100° C. using an IKA plate (model RCT Basic). The stirring speed was set at 250 rpm. The mixtures were stirred until homogenous, after which the magnetic stir bar was removed from each vial. The vials were then removed from the heating block and allowed to cool and solidify at ambient conditions with the caps screwed tightly on. The samples thus obtained are referred to as solidified samples in the remainder of this text.

[0073] Example 4: Purity assessment The purity was checked using the European Pharmacopoeia 8.0 monograph on vaselinum album (paraffin, white soft). Using this method, the commercially available components (SX50, Waxy Raffinate, Risella X430) were confirmed to be free of polycyclic aromatic hydrocarbons (PCAH) in this protocol. Subsequently, the subject of the present invention (isomerized Fischer-Tropsch derived wax with freezing points of 80°C and 70°C) was also tested and shown to be free of PCAH. In addition, the mixture from Example 3 was also subjected to the protocol and shown to be free of PCAH within the scope of the European Pharmacopoeia 8.0 monograph on vaselinum album (paraffin, white soft).

[0074] Example 5: Coating Test Protocol Those skilled in the art will appreciate that practical application of petroleum jelly requires spreading the jelly to form a layer on the skin.

[0075] The following protocol (hereafter referred to as the smear test) was established: While wearing nitrile rubber gloves, a spatula was used to transfer a small amount of petroleum jelly (approximately 0.2 grams) onto the index finger of one hand. The index and middle fingers of the other hand were used to smear the petroleum jelly onto the extended index and middle fingers of both hands.

[0076] The application test protocol was repeated five times with the commercial references from Example 2. Vaseline® felt the softest composition between the fingers and was the easiest to apply according to the application test protocol. The following order was established from easiest to requiring more effort to apply and spread: Vaseline®, Carisma Jelly SilkySoft, SnowWhite XH, Merkur 546. This range of commercial samples was used within the application test protocol. Petroleum jelly compositions tested for application that fell within this range were considered acceptable.

[0077] Example 6: Appearance evaluation The colour of the different petroleum jellies was evaluated according to the European Pharmacopoeia 8.0 monograph on vaselinum album (paraffin, white soft), and vaselinum flavum (paraffin, yellow soft).

[0078] The reference samples were evaluated as follows: Vaseline® is classified as a yellow petroleum jelly, and Charisma Jelly SilkySoft, SnowWhite XH, and Merkur 546 are classified as white petroleum jellies.

[0079] The composition of Example 3 was then investigated with the following results: The molten sample was classifiable as a white petroleum jelly.

[0080] The solidified examples could also be classified as white, very similar to the commercial sample SnowWhite XH, and significantly different from the yellowish Vaseline®.

[0081] Example 7: Odor evaluation The examples presented here have a slight paraffin odor, very similar to the commercial examples. No obvious odor was detected.

[0082] Example 8: Thermal properties Differential scanning calorimetry (DSC) traces were recorded using a TA Instruments Q2000 equipped with a Tzero sealed aluminum pan containing approximately 3-5 mg of sample. Samples were analyzed from -70 to 110 °C with heating and cooling rates of 3 K / min.

[0083] The melting point of the droplets was determined using TA Instruments Universal Analysis software by performing a running integral on the second heating curve from -40 to 100°C and then taking the temperature at which 95.0% of the material had melted. The freezing point was determined using TA Instruments Universal Analysis software by performing a running integral on the first cooling curve from 85 to -40°C and then taking the temperature at which 2.1% of the material had crystallized.

[0084] Using the above methodology on the commercial sample of Example 2, results were obtained that are comparable to the reported values ​​found in the specifications for the commercial product of Example 2. These DSC results differ by up to 3° C. compared to the reported values ​​for the melting point of the droplets of the commercial product, while the measured freezing point differs by up to 2° C. The comparison is reported in Table 2. [Table 2]

[0085] Example 9: Viscosity Measurements Viscosity was measured using a TA Instruments Discovery HR-2 rheometer equipped with a Peltier temperature system and a 60 mm parallel plate geometry. Approximately 2.5 mL of molten sample was transferred to the rheometer set at 100° C. The gap was set at 1000 μm. The sample was run at 5 points per decade with a 0.01 s -1 ~500 seconds -1 The analysis was performed using a steady-state flow sweep of about 100 seconds. -1 The measured plateau value was recorded as the dynamic viscosity. The dynamic viscosity value was divided by the density of the formulation to obtain the kinematic viscosity value.

[0086] Example 10: Stability evaluation The stability of the formulations was visually inspected for syneresis after storage at ambient conditions for up to 1 year. The formulations from Example 3 were kept intact in one of the closed vials in which they were prepared. Approximately 0.5 grams of material was scooped from the second vial using a spatula, and then the vial was closed again using a screw cap. This second vial was then visually inspected for syneresis after storage at ambient conditions for up to 1 year.

[0087] Example 11: Petroleum jelly formulation obtained Table 3 shows the petroleum jelly formulations prepared according to the procedure described in Example 3. [Table 3]

[0088] Example 12: Evaluation of the resulting petroleum jelly formulations Table 4 shows the spreadability, drop melting point, freezing point, kinetic viscosity, storage stability, and post-scoop stability of the petroleum jelly formulations as shown in Table 3. [Table 4]

[0089] Consideration From Example 12 it is clear that all compositions tested meet the requirements for stability both during storage and when tested by scooping. In pharmaceutical and cosmetic use, for example, petroleum jelly applied by painting for skin protection. All compositions were subjected to the test procedure described in Example 5 and the results obtained are tabulated in Example 12. For convenience, these results are reproduced in Figure 2, where the compositions are shown as a bar graph (% by weight).

[0090] The framed composition did not pass the coatability criteria set forth in Example 5.

[0091] Those skilled in the art will easily observe the encouraging results that MCW-1 (composition 13) can be spread as a petroleum jelly without further addition of wax or oil. When 10% or 20% by weight of WAX-1 is added to MCW-1 (compositions 12 and 10), the spreadability test can no longer be successfully passed. In composition 8 with 20% by weight of WAX-1, it is still not good when only 10% by weight of OIL-1 is added, but spreadability is obtained again when 40% by weight of OIL-1 is added, as shown by composition 5. Composition 3 is a further illustration of a spreadable petroleum jelly with 20% by weight of WAX-1 and a large fraction of oil: 48% by weight of OIL-2. At 40% by weight of WAX-1 and 35% by weight of OIL-2, the petroleum jelly with MCW-1 could not be spread (composition 1).

[0092] The microcrystalline wax MCW-2 of the present invention is not a spreadable petroleum jelly by itself, as can be seen from composition 14, and even with the addition of 20% by weight of WAX-1 (composition 12), it still cannot pass the spreadability test. Further partial replacement of MCW-1 by oil (10% by weight of OIL-1), as shown by composition 9, is another example of a spreadable petroleum jelly. Spreadability is maintained by a larger fraction of OIL-1: 30% by weight in composition 7 and 40% by weight in composition 6. Composition 4 is a further illustration of a petroleum jelly based on MCW-2 with 20% by weight of WAX-1 and even 48% of OIL-2. Composition 2 shows a spreadable composition based on MCW-2 with a large fraction of wax: 40% by weight of WAX-1. Finally, composition 15, a mixture of MCW-1 and MCW-2, successfully passed the spreadability test in the presence of WAX-1 and OIL-1.

[0093] In summary, the microcrystalline wax of the present invention provides a spreadable and stable formulation of petroleum jelly according to the criteria according to Examples 5 and 10. Those skilled in the art will appreciate that a wide range of formulation latitude is disclosed in the present invention since it is shown that petroleum jelly can consist entirely of microcrystalline wax (composition 13) or can consist partially, e.g., 25% by weight in composition 2. In addition, exemplary compositions are presented containing up to 40% by weight of wax (composition 2) and up to 48% by weight of oil (compositions 3 and 4).

Claims

1. A microcrystalline wax having a penetration of greater than 1 at 25°C according to ASTM D-1321, a crystallinity of 5-70% according to XRD, an initial boiling point of less than 500°C, a freezing point in the range of 60-120°C, and an oil content of greater than 2% by weight according to ASTM D-721, said microcrystalline wax having a maximum C40 fraction with at least 5% by weight of multi-methyl branched paraffins as determined by GCxGC and having molecules with a carbon number greater than 120.

2. 2. The microcrystalline wax according to claim 1, having an initial boiling point of greater than 100°C.

3. 3. The microcrystalline wax according to claim 1, which has a weight ratio of isoalkanes greater than the weight ratio of n-alkanes.

4. 1. A process for preparing a microcrystalline wax, said process comprising at least the following steps: (a) providing an FT wax having a carbon chain length distribution ranging from 20 to greater than 120 and a crystallinity according to XRD of greater than 75%, wherein at least 1 wt. % of said FT wax has a carbon chain length greater than 120; (b) a pore size of 5-7 angstroms and at least 25% SiO 2 / AlO 3 1. A process for the isomerization of said FT wax at a temperature in the range of 200-400° C., a pressure of 1-25 MPa, and a WHSV of 0.1-5 kg / l / hr using a catalyst comprising a molecular sieve having a ratio of 0.1 to 0.5% by weight of a Group VIII metal, and a catalyst having ...

5. a Fischer-Tropsch derived wax; 2. A petroleum jelly comprising the microcrystalline wax of claim 1 further comprising a Fischer-Tropsch derived waxy raffinate or a Fischer-Tropsch derived base oil.

6. 6. The petroleum jelly of claim 5, wherein said Fischer-Tropsch derived wax has a freezing point of 50°C.

7. 7. The petroleum jelly of claim 5 or 6, wherein the amount of microcrystalline wax is 20% or more but less than 100% by weight, the amount of Fischer-Tropsch derived wax is greater than 0% but less than 50% by weight, and the amount of waxy raffinate or base oil is greater than 0% but less than 50% by weight, based on the total amount of microcrystalline paraffin, Fischer-Tropsch derived wax, and waxy raffinate or base oil in the petroleum jelly.

8. 8. Use of the petroleum jelly according to claim 7 in a cosmetic product, a pharmaceutical product, a product for filling cables or a filled cable product.

9. 2. Use of the microcrystalline wax according to claim 1 in petroleum jelly, hot melt adhesives, as a gloss enhancer, car and shoe polish, as emulsion and PVC reactor protection.

Citation Information

Patent Citations

  • petroleum jelly cream

    JP1997501942A

  • Solid cosmetic

    JP2002348204A

  • Microcrystalline paraffins

    JP2004529192A

  • Manufacturing method of microcrystalline wax

    JP2004534124A

  • Method for Producing Base Oils from Fischer-Tropsch Synthetic Products

    JP2009513496A